Asia and the United States after 9/11: Primacy and Partnership in the Pacific - Tay, Simon S.C. (Tufts Archival Research Center, 2005)
Volume 28, Issue 1. Winter Simon Tay analyzes how U.S. policy on counterterrorism and the war in Iraq have influenced U.S.-Asian relations as well as how individual Asian nations are reacting to increased regional terrorist threats.